2014
DOI: 10.1155/2014/481392
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated G-CSF Inhibits Blood Cell Depletion, Increases Platelets, Blocks Splenomegaly, and Improves Survival after Whole-Body Ionizing Irradiation but Not after Irradiation Combined with Burn

Abstract: Exposure to ionizing radiation alone (radiation injury, RI) or combined with traumatic tissue injury (radiation combined injury, CI) is a crucial life-threatening factor in nuclear and radiological accidents. As demonstrated in animal models, CI results in greater mortality than RI. In our laboratory, we found that B6D2F1/J female mice exposed to 60Co-γ-photon radiation followed by 15% total-body-surface-area skin burns experienced an increment of 18% higher mortality over a 30-day observation period compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
78
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(87 citation statements)
references
References 32 publications
9
78
0
Order By: Relevance
“…2 Further definitive results involving topical gentamicin application on wounds along with oral levofloxacin administration, two broad-spectrum antibiotics, demonstrate the inability of this class of drugs to positively affect survival after combined injury in a manner as robust as ciprofloxacin (38). These data, in combination with our current and previously published results, support the hypothesis that the effect of ciprofloxacin treatment after combined injury is not simply protection from sepsis, and that it does involve a number of complementary mechanisms, all leading to improved health and survival (6,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…2 Further definitive results involving topical gentamicin application on wounds along with oral levofloxacin administration, two broad-spectrum antibiotics, demonstrate the inability of this class of drugs to positively affect survival after combined injury in a manner as robust as ciprofloxacin (38). These data, in combination with our current and previously published results, support the hypothesis that the effect of ciprofloxacin treatment after combined injury is not simply protection from sepsis, and that it does involve a number of complementary mechanisms, all leading to improved health and survival (6,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…The strain differences outlined above suggest that radiation countermeasures should be tested in more than one mouse strain; in terms of countermeasures for ARS, one resistant (C57BL/6 or CD2F1) and another sensitive strain (C3H/HeN or BALB/c) should be tested for other 'delayed-type' response patterns, specific, pathology-susceptible strains need to be considered and utilized in testing. The mouse model has been used to study combined injury (radiation plus wound, burn, or hemorrhage) as well as for the evaluation of countermeasures effective against combined injuries (Kiang et al 2012(Kiang et al , 2014aElliott et al 2015). Efficacy of several radiation countermeasures such as captopril, PEGylated G-CSF, ghrelin, ciprofloxacin etc., has been established using the combined injury model in mice (Jiao et al 2009;Kiang et al 2010Kiang et al , 2014bSwift et al 2015).…”
Section: Micementioning
confidence: 99%
“…An additional study demonstrated that PEGylated G-CSF limits the severity of the radiation-induced cytopenias in the rodent ARS model. However, this modified recombinant unfortunately appears to be less efficacious than G-CSF in treating irradiated animals with significant skin burns (15% total body surface area skin burns) (Kiang et al 2014a). Similar to G-CSF, PEGylated G-CSF has also been used in several radiation accident victims with positive outcomes (Reeves 2014;Singh et al 2015a).…”
Section: Pegylated G-csf/neulasta/pegylated Filgrastimmentioning
confidence: 99%
“…In a recent study it has been observed that G-CSF appears to protect both irradiated and combined injury (irradiated and wounded) mice. G-CSF has not been tested in a murine combined injury model of irradiation and burn [71]. Contrary to the above positive findings of therapeutic effectiveness of these recombinants, there is one report in a mouse model where the use of G-CSF did not show a survival benefit [72].…”
Section: Studies With G-csfmentioning
confidence: 99%
“…The 'one low dose administration' schedule is an attractive attribute of a radiation countermeasure given the logistical challenges of medical care in a mass-casualty scenario. Recently, it has been demonstrated that pegylated G-CSF inhibits blood cell depletion, surprisingly increases platelets, blocks splenomegaly, and improves survival after whole-body ionizing irradiation but not after irradiation combined with skin burns (15% total-body-surface-area skin burns) in mice [71].…”
Section: Studies With Pegylated G-csfmentioning
confidence: 99%